Tracking devices and physical performance analysis in team sports: a comprehensive framework for research—trends and future directions - Ferraz, António; Duarte-Mendes, Pedro; Sarmento, Hugo; Valente-Dos-Santos, João; Travassos, Bruno (Frontiers in Sports and Active Living, 2023)
Background: Tracking devices, such as global (GPS) and local (LPS) position systems combined with physiological measurements, have become reliable tools to characterize movement patterns, assessing athletes' external (EL), internal load (IL), fatigue, and performance in team sports. This scoping review aimed to provide a comprehensive understanding of the applicability of tracking systems in physical performance analysis within team sports and athlete´s well-being based on research strategies and combined variables. Methods: A systematic search was conducted in PubMed, Web of Knowledge, and Scopus databases according to PRISMA guidelines. The 79 studies that were reviewed met the following criteria: (1) contained relevant data regarding elite athletes´ performance; (2) athletes’ EL and IL; (3) were written in the English language; (4) were only related to team sports. Results: The findings indicate that tracking technology has been engaged in several research fields, including performance analysis, training versus match load management, injuries, and nutrition through characterization and correlational studies. Metrics, primarily focused on kinematics and mechanical EL aspects, have been employed in combination with IL data to analyze athletes' performance. However, the lack of an integrative model for the analysis and integration of EL and IL metrics within each team sport suggests an interesting direction for further research. Conclusion: There is a need for coherence between the methods and research goals on performance analysis. The development of a framework that guides experimental studies is highly recommended, particularly on manipulating metrics analyzed between training and match sessions, injury prevention, and nutrition. This will lead to the development of most applied sports science research to improve athletes’ preparation and decision-making based on reliable data.